PELAYANAN KESEHATAN DAN PENGOBATAN PENYAKIT PADA POPULASI SAPI TARO DALAM MENDUKUNG PROGRAM KONSERVASI DI DESA TARO, KECAMATAN TEGALALANG, KABUPATEN GIANYAR, BALI - Susari, Ni Nyoman Werdi (Buletin Udayana Mengabdi, 2020)
Cattle are a species that can be found in all parts of the world, including Indonesia. This community service activity carried out in Taro Village, Tegalalang District, Gianyar Regency. The aimed of this health services is to maintaining the taro cattle population as a conservation effort.Taro cattle is one of the germplasm that is unique to Bali, apart from Balinese cattle. The method used in this community service is in the form of health services carried out in the taro white cow shed area, in Taro Kaja Village. Services are provided by providing vaccine, vitamins, worm medicine to healthy livestock and treating sick cattle, spraying in the cattle cage, as well as conducting discussions with breeders regarding the management of taro white cattle maintenance, as well as other problems such as common diseases in cattle. and the taro white cow problem. It is hoped that through this service, the cattle healthy will be improve and disease incidence will be decrease, we can give information about the management of reproductive for the taro’s. This programs is important to increasing public knowledge to maintain taro’s population, that conservation programs can be carried out.